Relationship of cyanobacterial abundance and chlorophyll-a concentration in Lake Danao, Ormoc City, Leyte, Philippines - Neis, Liza Mae V.; Parilla, Richard B. (2022)
Lakes are continuously being degraded due to cultural eutrophication as a result of excessive nutrients. Cyanobacteria are known indicators of eutrophication and some species could cause harmful algal blooms (HABs). Monotoring of cyanobacteria requires a faster and more efficient method such as chlorophyll-a (chl-a) analysis. This study aimed to determine the composition and abundance of cyanobacterial density and chl-a were assessed bimonthly from five sampling stations in Lake Danao from March to May, and July to September 2021. Physicochemical parameters such as DO, pH, conductivity, temperature, transparency, light intensity, nitrates, nitrites, and phosphates were also measured. Pearson correlation and linear regression were used to establish the relationship and a linear regression model. Lake Danao houses 6 cyanobacteria species, with Gloeocapsa as the most abundant. Two HAB-causing cyanobacteria, Microcystis and Oscillatoria, were observed in the lake in low counts. A strong positive relationship between chl-a and cyanobacterial density (r=0.877) was observed. Phosphates was found to affect this relationship as there is higher densities of cyanobacteria with low chl-a content at lower phosphate levels. Moreover, chl-a was found to be an insufficient predictor of cyanobacterial density. The addition of water transparency has improved the predictive ability of the model by 10%, with a final R raised 2 value of 0.87. The established model is a simple predictive tool that could potentially be valuable in monitoring eutrophication and may serve as an early-warning signal for possible harmful algal bloom occurrence in the lake.
Undergraduate thesis (B. S. Biology) -- University of Philippines, Tacloban.
Keywords: Botany